Complete Genome Sequence of the Wild-Type Commensal Escherichia coli Strain SE15, Belonging to Phylogenetic Group B2 - Toh, Hidehiro (American Society for Microbiology (ASM), 2010)
Escherichia coli SE15 (O150:H5) is a human commensal bacterium recently isolated from feces of a healthy adult and classified into E. coli phylogenetic group B2, which includes the majority of extraintestinal pathogenic E. coli. Here, we report the finished and annotated genome sequence of this organism.